Pengaruh kompetensi dan integritas pada kualitas audit dengan key audit matters sebagai moderasi - Siti Halimah (LPMP Imperium, 2024)
This research aims to determine the influence of competency and integrity on audit quality with key audit matters as moderation at public accounting firms in DKI Jakarta that are active and registered with the Financial Services Authority (OJK). This research uses primary data with a survey method, namely distributing questionnaires with sample determination using a random sampling method, which 127 respondents used to spread across several Public Accounting Firms in DKI Jakarta. The data analysis method used in this research is the multiple regression method. This research shows that competence and integrity positively affect audit quality, and related moderating variables show that key audit matters (KAMs) cannot strengthen the relationship between competence and integrity on audit quality. Public interest statements Ensuring auditors' competency and integrity and effectively utilizing key matters (KAM) makes the audit process more transparent. This fosters greater public confidence in audited financial reports and ensures the reliability of company-provided information. Regulating the influence of competence and integrity on audit quality through KAM is expected to enhance transparency in financial information management, allowing for more informed public investment and financial decisions.